A novel framework for linking functional diversity of plants with other trophic levels for the quantification of ecosystem services. (14th May 2013) - Lavorel, Sandra; Storkey, Jonathan; Bardgett, Richard D.; de, Francesco; Berg, Matty P.; Le, Xavier; Moretti, Marco; Mulder, Christian; Pakeman, Robin J.; Díaz, Sandra; Harrington, Richard; Mason, Norman
Abstract A novel conceptual framework is presented that proposes to apply trait‐based approaches to predicting the impact of environmental change on ecosystem service delivery by multi‐trophic systems. Development of the framework was based on an extension of the response–effect trait approach to capture functional relationships that drive trophic interactions. The framework was populated with worked examples to demonstrate its flexibility and value for linking disparate data sources, identifying knowledge gaps and generating hypotheses for quantitative models.